Are retirees more satisfied? Anticipation and adaptation effects: a causal panel analysis of German statutory insured and civil pensioners - Joachim Merz (Leuphana Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2022)
This study contributes to the subjective well-being and retirement literature by quantifying life satisfaction before (4) and after retirement (9+) periods asking: Are retirees more satisfied? Fixed-effects and causal instrumental variables (IV) estimates with individual longitudinal data of the Socio-Economic Panel (SOEP, 33 waves) analyze anticipation and adaptation retirement effects of statutory insured and civil service pensioners in Germany. Main findings: The occupational situation absorbs a positive personal and family influence. There are positive anticipation effects before retirement followed by adaptation instantly when retired both for statutory insured and civil service pensioners. With neutral respectively negative post-retirement adaptation there is no longer positive retirement effect for both pensioner groups. In short: retirees are not more satisfied, a remarkable result both for statutory insured and civil service pensioners. – – Diese Studie trägt zur Literatur der Zufriedenheit und dem Renteneintritt mit einer Quantifizierung der Lebenszufriedenheit vor (4) und nach (9+) Rentenperioden bei und fragt: Sind Rentner zufriedener? Fixed-effects und kausale Instrumental Variablen (IV) Schätzungen mit individuellen Längsschnittdaten des Sozio-ökonomischen Panels (SOEP, 33 Wellen) analysieren Antizipations- und Adaptionseffekte des Renteneintritts von gesetzlich Versicherten und Pensionären in Deutschland. Hauptergebnis: Die berufliche Situation absorbiert einen positiven individuellen und familiären Einfluss. Es gibt positive Antizipationseffekte vor dem Renteneintritt gefolgt von Adaption direkt nach dem Renteneintritt sowohl für gesetzlich Versicherte als auch für Pensionäre. Mit neutraler respektive negativer Adaption gibt es keinen längeren positiven Renteneffekt für beide Ruhestandsgruppen. In Kürze: Rentner sind nicht zufriedener, ein bemerkenswertes Ergebnis für beide Gruppen, gesetzlich Versicherte und Pensionäre.
Keywords: I31; J26; C21; C23; 330; Retirement; statutory insured and civil service pensioners; life satisfaction/subjective well-being; anticipation and adaptation effects; robust fixed-effect regression; causality IV estimates; Socio-Economic Panel (SOEP); Germany; Renteneintritt; gesetzlich Versicherte und Pensionäre; Lebenszufriedenheit; Antizipations- und Adaptionseffekte; robuste fixed-effects Regression; kausale Instrumental Variablen (IV) Schätzungen; Sozio-oekonomisches Panel (SOEP); Deutschland